ADHERENCE TO NUTRITIONAL SUPPLEMENTATION, FOLLOW-UP CARE, AND LOST TO FOLLOW-UP IN POST BARIATRIC SURGERY PATIENTS - Wali, Muhammad Hassaan; Khava Bekova,; Noor Abdulla,; Simhachalam Gurugubelli,; Yi Mon Lin,; Devendar Banoth,; Samia Rauf Butt, (Journal of Ayub Medical College Abbottabad, 2024)
Background: With the global rise in obesity rates, bariatric surgery has emerged as an effective intervention for weight management and obesity-related comorbidities. Bariatric surgery offers transformative potential but demands lifelong adherence to multifaceted care, including nutritional supplementation and vigilant follow-up. Nutritional deficiencies affect 30% to 70% of patients, encompassing vital elements like vitamins (B12, D, folate), minerals (iron, zinc, calcium), and proteins, necessitating continuous monitoring to prevent complications. This comprehensive review explores the multifaceted challenges in post-bariatric surgery patient care, focusing on adherence to nutritional supplementation, follow-up care, and the prevalence of nutritional deficiencies. Methods: A systematic synthesis of relevant literature was conducted, encompassing studies examining post-operative care practices, adherence to prescribed multivitamin supplements (MVS), rates of follow-up, and nutritional deficiencies in bariatric surgery patients. Nine key studies were analyzed and synthesized to extract critical insights. Results: Findings revealed a complex landscape of post-bariatric surgery care, marked by both promise and pitfalls. Adherence to MVS regimens emerged as a significant challenge, influenced by factors such as forgetfulness, gastrointestinal side effects, cost concerns, and poor follow-up rate. Lost-to-follow-up rates varied across studies, raising concerns about the continuity of care. Nutritional deficiencies were prevalent, underscoring the importance of long-term monitoring. It highlights the need for tailored patient education, improved doctor-patient communication, and shared decision-making processes to enhance adherence and follow-up care. Conclusion: This review underscores the intricate nature of post-bariatric surgery patient care, emphasizing the critical role of adherence, follow-up, and nutritional monitoring. Disparities in care among different regions of the world with varying healthcare systems are acknowledged as a significant challenge; addressing these challenges necessitates a collaborative effort among healthcare providers, patients, and policymakers to optimize the long-term well-being of individuals who undergo bariatric surgery.